Kontribusi Kemampuan Wacana dan Kemampuan Berpikir Logis terhadap Keterampilan Mengedit Siswa Kelas IX SMP Negeri 12 Padang - Asvidyanti, Asvidyanti; Atmazaki, Atmazaki; Manaf, Ngusman Abdul (Journal of Education Language and Innovation, 2023)
The goal of this study is to explain the contribution of discourse ability, logical thinking, discourse ability, and logical thinking ability for IX grade student’s editing skill of 12 Junior High School Padang. This is quantitative study with descriptive method and correlational design using. The population of this study are the 228 students of IX grade students at SMP Negeri 12 Padang. Samples comprises of 70 students were obtained using Cluster random sampling. The data is analyzed by using Pearson Product Moment (PPM) corelation test, multiple correlation tes, t test, F test, determinant coefficient formula to know how much independent variables contribute to dependent variables either alone or collectively. The result of this study is as follows. (1) Discourse ability gives significant 64% for editing skills because tcount > ttable or 11 > 1,671. (2) Logical thinking ability gives significant contribution 68,89% for editing skills because tcount > ttable or 12,21 > 1,671. (3) Discourse ability and logical thinking give significant contribution 70,56% for editing skill because F count > F table or 153,391 > 3,14. So, it could be concluded that discourse ability and logical thinking, either alone or collectively give significant contribution for editing skill of IX grade students of 12 Junior High School Padang.